Prevalence of neural tube defects, maternal HIV status, and antiretroviral therapy from a hospital‐based birth defect surveillance in Kampala, Uganda. Issue 3 (11th November 2021) - Barlow‐Mosha, Linda; Serunjogi, Robert; Kalibbala, Dennis; Mumpe‐Mwanja, Daniel; Williamson, Dhelia; Valencia, Diana; Tinker, Sarah C.; Matovu, Joyce Namale; Moore, Cynthia A.; Adler, Michelle R.; Nelson, Lisa; Nankunda, Jolly; et al.
Abstract: Background: The estimated prevalence of neural tube defects (NTDs) in Africa is 11.7 per 10, 000 live births; however, data on the impact of antiretroviral therapy (ART) during pregnancy and the risk for birth defects in Africa are limited. Methods: Data from a hospital‐based surveillance program at four hospitals in Kampala, Uganda were used to estimate the baseline prevalence of NTDs and assess potential associations with HIV status and ART use. All live births, stillbirths, and spontaneous abortions delivered at the participating hospitals affected with selected birth defects between August 2015 and December 2018 were included. Trained midwives collected data from hospital records, maternal interviews, photographs, and narrative descriptions of birth defects. We estimated NTD prevalence per 10, 000 births (live, stillbirths, spontaneous abortions), prevalence ratios, and 95% confidence intervals (CIs). Results: A total of 110, 752 births from 107, 133 women were included in the analysis; 9, 394 (8.8%) women were HIV‐infected and among those with HIV infection, 95.6% ( n  = 8, 977) were on ART at delivery. Overall, 109 births were affected with NTDs, giving a prevalence of 9.8 (95% CI [8.2, 11.9]). Spina bifida ( n  = 63) was the most common type of NTD, with a prevalence of 5.7 (95% CI [4.4, 7.3]), followed by anencephaly ( n  = 31), with a prevalence of 2.8 (95% CI [2.0, 4.0]). Conclusion: The prevalence of NTDs among births in Kampala, Uganda is consistent with current estimates for Africa. With the continued introduction of new medications that may be taken during pregnancy, sustainable birth defect surveillance systems and pharmacovigilance are indicated.